Dialogic Communication under Algorithmic Mediation in TikTok Live: A Case Study of Religious Services - Rayyan Halim Yuwono; Nur’annafi Farni Syam Maella; Harliantara (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study examines how algorithm-based dialogic communication operates in TikTok Live as a form of digital religious service at the Bulukerto Office of Religious Affairs (KUA). The research aims to analyze interaction patterns, the role of algorithmic mediation, and the adaptation of dialogic communication principles in platform-based environments. Using a qualitative case study approach, data were collected through in-depth interviews with the TikTok Live host and non-participant observation of five live sessions. The data were analyzed using thematic analysis to identify recurring interaction structures. The findings reveal that communication does not occur randomly but follows a structured pattern consisting of three interconnected mechanisms: responsiveness, amplification, and selectivity. Responsiveness enables real-time interaction, amplification increases visibility through engagement signals, and selectivity filters which interactions receive attention. These mechanisms form an iterative communication system shaped by both human agency and algorithmic governance. This study contributes to the development of communication theory by integrating dialogic communication with algorithmic mediation into a conceptual model. Practically, the findings provide insights for public institutions in optimizing digital religious services within algorithm-driven platforms.